Selective serotonin reuptake inhibitors use and dental implant failure: A call for awareness and caution - Amjad, Amna; Rehman, Hafsa (Journal of the Pakistan Medical Association, 2024)
Dear Editor, I am writing to express my concerns regarding the possible negative impact of selective serotonin reuptake inhibitor (SSRI) use on dental implants. Globally, depression is on the rise, especially in low-income countries (1). SSRIs are the most commonly prescribed antidepressants worldwide and may interfere with bone metabolism, which can affect dental implant success (2). According to several studies, there was a higher risk of dental implant failure and peri-implant bone loss in SSRIS users compared to non-SSRIS users, and the association was found to be statistically significant (3–5). ). Smoking may also further increase this risk (3,4). Also, a decrease in the survival rates of dental implants was reported (2,6). However, some studies found no statistically significant association between SSRIS use and dental implant failure (7,8). Therefore, further studies were needed to evaluate the effects of different dosages and durations of selective serotonin reuptake inhibitors on dental implant outcomes. This highlights an important issue, especially for countries like Pakistan, where the prevalence of depressive disorders ranges from 20% to 60% and smoking is common (9). This can be due to the prevailing economic crisis in the country and the overall shortage of job opportunities, which leads to an increase in poverty rates that can trigger stress and some serious depressive disorders. Dental implants are a widely used intervention for edentulous patients who are suffering from a reduced quality of life due to tooth loss. Dental implant failure can cause physical, emotional, and financial distress for both patients and dentists. Therefore, it is suggested that readers be aware of these potential risks, take proper precautions, and consult their doctors before taking SSRIs or any other medication that can affect bone health. We urge dentists to take a proper history regarding SSRI use and consider an alternate class of anti-depressants for patients with dental implants.